Characterization of the penicillin G acylase from Bacillus megaterium ATCC 14945 - Souza,Vanessa Ribeiro de (2005)
The purpose of this work was to characterize the enzyme penicillin G acylase (PGA) produced by Bacillus megaterium. Purification of the enzyme by ultra/diafiltration did not allow the detection of the PGA band by SDS-PAGE electrophoresis due to the high content of remaining proteins. However, using the DNA of the microorganism, it was possible to replicate the genes of the two B. megaterium PGA reported in literature, showing that the enzyme consisted of two sub-units, having 245 and 537 amino acids each and an average molecular mass of 26950 and 59070 Da, respectively. The parameters studied were: 1) the influence of temperature in the 25-60(0)C range, 2) pH in the 5-10 range and 3) substrate concentration, this was tested to obtain results on the Penicillin G hydrolysis reaction rate, using the initial velocities approach. The maximum hydrolysis rate was obtained at 37ºC and pH 8.0. The Michaelis-Menten model fitted well, resulting in estimated Km and Vmax parameters values of 1.83 mM and 0.165*10-3 mmol/min/UI, respectively.